Health problems and work conditions of printers in small-scale enterprises in Ibadan, southwest Nigeria (2013)
Background: Printers work in small scale enterprises located within residential and commercial areas of various cities in Nigeria with little regulation of work premises and work practices. Aims: A cross-sectional study was designed to assess the work conditions and health problems of printers. Methods: All printers at the workshops visited were interviewed after obtaining informed consent Socio- demographic characteristics, occupational hazards, current health problems and injuries were recorded. Printers' hands were examined for dermatitis. A check list was applied at each workshop to assess the work environment and welfare and safety facilities. Results: A total of 369 printers were interviewed in 224 workshops. Occupational hazards reported were sharp edges of machinery 210 (74%), chemicals 41(15%) and generator fitmes 33(1.6%). Sixty printers (16%) had work- related accidents in the year preceding the study. 'Finger caught in machine' accounted for 70%> of accidents. Injuries reported included lacerations, 49 (57%), bruises and cuts 45(52%) and finger nail torn off, 8 (9%). Current health problems were skin conditions reported by 21(5%), respiratory symptoms 46 (12%) predominantly sneezing, cough and runny nose, musculoskeletal disorders 103 (28%), predominantly low back pain, neurological symptoms, 60 (16 %) predominantly headaches and eye problems, 32 (9%) predominantly poor vision. Hand dermatitis was observed in 17(5%>) printers. Ventilation was inadequate in 100 (47%) workshops; 17 (8%) had first aid boxes and general housekeeping was poor in 33 (16%) workshops. Conclusions: Health education interventions, gloi’e use, first aid facilities, improvement of ventilation and general housekeeping are needed to address these problems.